(untitled) (PerCursos, 2021)
The rupture of the Fundão tailings dam in the town of Mariana/Minas Gerais, in November 2015, contaminated the Rio Doce and affected drastically the Krenak, people who live on the banks of this river. This work aims to analyze the statements published by the Krenak leaders and intellectuals about the rupture of the dam, through discussions about modernity and coloniality, developed by authors of decolonial Latin American thinking. The methodology used is qualitative, based on bibliographic analysis and content analysis (BARDIN, 2016). The time frame encompasses the years from 2015 to 2020. The analysis demonstrated the Krenak’s narratives about the disaster doesn´t consider it as an isolated fact, but as another violence within the history of rights violations, that they have suffered since the beginning of colonization to the present. The senses and perceptions of the Krenak people converge to a profound critique of the capitalist mode of production; the colonial narrative; the view of nature as a resource; the crisis of ethical values. Between antagonistic worlds, Krenak indigenous thought converges with the elements and categories of the decolonial movement for the possibility of another way of living.